Evaluation of efficacy and safety of cryotherapy in benign and premalignant cervical lesion - Patel, Kishankumar D.; Karnavat, Ronak D.; Viramgama, Dimple G.; Dalal, Roma K. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2021)
Background: Cervical cancer ranks 3rd leading cause of cancer in the world. Cervical erosion is mostly asymptomatic in women but when symptoms like postcoital bleeding and vaginal discharge occur in the presence of cervical erosion, it becomes important to identify whether the erosion is a benign lesion or CIN or cancer by means of PAP smear and Biopsy. Treatment for benign and precancerous lesion can be provided by ablative or excisional methods. Cryotherapy was reliably used to treat cervical lesions. Methods: Women among 18 to 60 years of age attending outpatient department who had history of chronic discharge per vaginum, postcoital bleeding, dyspareunia, chronic pelvic pain. Patients were divided in two by PAP smear in erosion with inflammatory changes and presence of low grade squamous intraepithelial lesion. Cryotherapy was performed using double-freeze single session procedure. Each patient was followed up at 2, 6 and at 12 weeks. Complications and patients’ satisfaction were recorded and compared to calculate cure rate of symptoms, healing of lesion. Results: The healing efficacy of cryotherapy at 6th and 12th week was 87.8% and 91.1% respectively. Cryotherapy had high satisfaction rate. The cure rate was not affected by location of lesion and size of lesion in both inflammation and LSIL. Conclusions: Cryotherapy is an effective method for treatment of cervical erosion and effectively eliminates symptoms. Patients were highly satisfied. Cryotherapy is cheap, easy, and safe treatment. It is suitable for both hospital and office-based practice.